The ORION statement: guidelines for transparent reporting of outbreak reports and intervention studies of nosocomial infection. - Stone, S; Cooper, B; Kibbler, C; Cookson, B; Roberts, J; Medley, G; Duckworth, G; Lai, R; Ebrahim, S; Brown, E; Wiffen, P; Davey, P (2007)
The quality of research in hospital epidemiology (infection control) must be improved to be robust enough to influence policy and practice. In order to raise the standards of research and publication, a CONSORT equivalent for these largely quasi-experimental studies has been prepared by the authors of two relevant systematic reviews, following consultation with learned societies, editors of journals and researchers. It consists of a 22 item checklist, and a summary table. The emphasis is on transparency to improve the quality of reporting and on the use of appropriate statistical techniques. The statement has been endorsed by a number of professional special interest groups and societies. Like CONSORT, ORION should be considered a 'work in progress', which requires ongoing dialogue for successful promotion and dissemination. The statement is therefore offered for further public discussion. Journals and research councils are strongly recommended to incorporate it into their submission and reviewing processes. Feedback to the authors is encouraged and the statement will be revised in 2 years.